2022
DOI: 10.1097/sla.0000000000005671
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Axillary Lymph Node Dissection and Sentinel Lymph Node Biopsy on Upper Limb Morbidity in Breast Cancer Patients

Abstract: Objective: To evaluate the impact of axillary lymph node dissection (ALND) and sentinel lymph node biopsy (SLNB) on upper limb (UL) morbidity in breast cancer patients. Background: Axillary de-escalation is motivated by a desire to reduce harm of ALND. Understanding the impact of axillary surgery and disparities in operative procedures on postoperative arm morbidity would better direct resources to the point of need and cement the need for deescalation strategies. Methods: Embase, MEDLINE, CINAHL, and PsychINF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 76 publications
0
45
0
Order By: Relevance
“…[24] Retrospective studies and meta-analyses have demonstrated that there is still a certain morbidity of upper limb complications after SLNB surgery, the most common is axillary pain, which torments more than 10 percent of patients. [25][26][27] The reason may be largely due to excessive exploration of SLN. Previous study has suggested that, in a small minority of patients, the SLN for the breast and upper limb may be at the same station.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Retrospective studies and meta-analyses have demonstrated that there is still a certain morbidity of upper limb complications after SLNB surgery, the most common is axillary pain, which torments more than 10 percent of patients. [25][26][27] The reason may be largely due to excessive exploration of SLN. Previous study has suggested that, in a small minority of patients, the SLN for the breast and upper limb may be at the same station.…”
Section: Discussionmentioning
confidence: 99%
“…Rockson et al reported that the presence of hypertension in 51 of 130 patients seemed to predispose the development of lymphedema (P<0.005) (26). Several studies also reported that axillary radiotherapy increase the risk of lymphedema from 1.91-to 4.285-fold (19,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…2023;277:572-580. 6 This study investigates the impact of axillary lymph node dissection (ALND) and sentinel lymph node biopsy on upper extremity morbidity in patients with breast cancer. Included studies were objective-based, using validated tools for lymphedema, range of motion, and strength.…”
Section: Impact Of Axillary Lymph Node Dissection and Sentinel Lymph ...mentioning
confidence: 99%